Assessment Of Maintainability Design Criteria On Government Hospital Buildings - Othman, Nur Liyana (2018)
Building maintainability is an indispensable aspect that needs to be considered in order to achieve good building performance and reduce maintenance cost. Maintainability Design Criteria (MDC) is a specific design requirement to address ease of maintenance work aspects and minimise the occurrence of building defects towards achieving optimal building performance within minimum cost throughout the building’s life cycle. MDC is one of the key areas to improve the management of government hospital buildings. The objectives of the study are 1) to assess the MDC in government hospital buildings, 2) to examine an application of MDC in government hospital buildings, and 3) to develop a checklist of MDC for government hospital buildings. To achieve the objectives, the case study method consists of secondary documents reviewed, focus group interview, survey interview and face-to-face interview to elicit the information regarding the cases. The experts’ survey to validate the checklist was conducted. Two government hospitals namely Hospital Sultanah Bahiyah and Hospital Sultan Abdul Halim were selected as case studies. MDC for government hospitals has been measured through accessibility, suitability of materials and environmental. Data were analysed using case-oriented analysis and cross-case analysis. The findings of first objective shows there are different levels of MDC’s condition in government hospital buildings which require improvement to achieve higher maintainability. The second objective reveals an improper application of MDC in government hospital buildings due to lack of awareness and knowledge on maintainability, non-existence of formal procedure to guide the industry on the MDC and the missing clause on MDC in the contract documents. The third objective is to develop the formal checklist as alternative procedure to address MDC at the design stage and encompasses relevant design provision of MDC for government hospital buildings. In conclusion, the study found MDC is significant in achieving good building performance, reducing maintenance cost, diminishing the occurrence of defects and enhancing comfort to the end users in government hospital buildings.